Co-Teaching: From Lines of Action as a Means to Implement the Universal Design for Learning (UDL) - Segura Castillo, Mario Alberto (2026)
This essay stems from the project Pedagogical Experiences of a Group of Teachers in the Second Cycle of General Basic Education in the Implementation of the Second Principle of Universal Design for Learning (UDL) (Pr-725-C3-050-2023) carried out by the Institute of Educational Research of the University of Costa Rica (INIE-UCR). Specifically, it explores how co-teaching becomes a means of implementing inclusive education, as reflected in pedagogical mediation strategies based on the Universal Design for Learning (CAST, 2018). Therefore, the objective of this essay is to determine the impact of co-teaching on the support services in special education and on the teaching staff of the first and second cycles of General Basic Education, the definition of co-teaching prompts reflection on an innovative practice that goes beyond inclusive education by facilitating the implementation of Action Lines through Universal Design for Learning (CAST, 2024). It is concluded that, at the outset of implementation, both the teaching staff from Special Education support services and the teachers from the first and second educational cycles were unfamiliar with the concept of co-teaching, which led to considerable uncertainty in the initial stages.